Improving Students’ Lampung Script Writing Skills Through Using Online Word Cards - Heldawati Heldawati; Joko Sutrisno AB; Abdullah Abdullah (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2021)
This study aims to determine the use of online word cards in improving the quality of learning in Lampung literacy writing skills and to find out the increase in Lampung writing skills in students in class V MIN 4 Pringsewu. The problems raised in this study were 1) to find out the use of online word cards in improving the quality of learning of writing skills in Lampung literacy. 2) to find out the improvement in Lampung writing skills in class V MIN 4 Pringsewu. This research is a Classroom Action Research (CAR) with research subjects V MIN 4 Pringsewu. This research was conducted in two cycles. Researchers provide guidance as a collaborator to the fifth-grade teacher on the application of word cards to improve the writing skills of Lampung students in grade V which is still very low. Therefore, this research can be said to be collaborative class action research. The subjects of this study were 27 students. The results of the study can be concluded as follows: first, the word card media can improve the quality of the learning process of Lampung students' writing skills online for class V MIN 4 Pringsewu. Students experience changes in behavior (improvement) in online learning. Second, word cards can improve the product/results of Lampung students' writing skills online grade V MIN 4 Pringsewu. Improvement of product quality/results can be seen from the comparison of the average writing scores at the pre-action and post-cycle stage II.